2023
DOI: 10.3390/app13179632
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue: New Developments and Prospects in Clean and Renewable Energies

Alireza Dehghani-Sanij,
Farshad Moradi Kashkooli

Abstract: The world is facing ongoing and emerging energy challenges such as energy poverty for ~25% of the world’s population, limited fossil fuel resources, and the global environmental crisis [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In the power industry, fossil energy is still dominant, which results in significant carbon emissions. The statistics of carbon emissions are typically based on macro data, several studies have identified the generational factors related to carbon emissions and have proposed carbon reduction methods based on the generational side [4][5][6]. Reference [6] considers the influence of environmental operating characteristics on carbon emissions of gas turbine power plants, which will help to reduce carbon dioxide emissions.…”
Section: ∼ Y I Predicted Values Of the Carbon Emission Factors At Nod...mentioning
confidence: 99%
“…In the power industry, fossil energy is still dominant, which results in significant carbon emissions. The statistics of carbon emissions are typically based on macro data, several studies have identified the generational factors related to carbon emissions and have proposed carbon reduction methods based on the generational side [4][5][6]. Reference [6] considers the influence of environmental operating characteristics on carbon emissions of gas turbine power plants, which will help to reduce carbon dioxide emissions.…”
Section: ∼ Y I Predicted Values Of the Carbon Emission Factors At Nod...mentioning
confidence: 99%
“…In addition, energy is seen as a pivotal concern in the economic advancement of countries [13], and on a yearly basis, energy consumption in developing countries grows by 5% on average [14]. Consequently, renewable energy sources have garnered significant attention globally in recent years [15] and solar energy is the leading renewable energy source [16]; this is predicted to significantly impact energy security and environmental problems in both emerging and established countries [17]. Solar power is the primary form of renewable energy utilized for generating electricity [18], operating solar collectors [19][20][21], cooking with solar energy [22,23], drying with solar energy [24], combining solar and biomass energy [24], and heating metals [24].…”
Section: Introductionmentioning
confidence: 99%